METHOD FOR EVALUATING THE EFFICIENCY OF UPGRADING SPECIALIZED INFORMATION SYSTEMS - Alina Mikhnova; Dmutro Mikhnov; Kateryna Chyrkova (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the study in the article is the process of modernization of automated workingplaces of specialized information systems of the organization. The purpose of the work is to develop a method for evaluating the efficiency of modernization of automated workingplaces specialized information systems, which allows, on the basis of analysis of the degree of automation of workingplaces and its impact on the performance of an organization, to determine a rational variant of the project solution in the context of budget constraints. The following tasks are solved in the article: analysis of the peculiarities of evaluating the effectiveness of specialized information systems; substantiation of influence of completeness and reliability of data of receiving information from automated workingplaces on the performance indicators of the organization; development of forming stages of the method of estimating the efficiency of modernization of automated workingplaces; practical testing of the method. The following methods are used: system analysis, functional-cost analysis, modeling of decision making. The following results were obtained: a method of evaluating the effectiveness of modernization of automated workingplaces of specialized information systems, which can be applied to organizations whose performance indicators are directly dependent on the completeness and reliability of the primary data of business processes, is proposed;; the calculation of the rational version of the modernization of the automated workingplaces of the specialized information system of the regional blood service center with limited financing of the system modernization using the method was performed. Conclusions: application of the method of efficiency estimation of modernization at the stage of planning of expenses for improvement of the automated workingplaces of the specialized information system of the organization will allow to identify the automated workingplaces on which the increase of degree of automation will lead to the most significant potential values of activity indicators of the organization. The practical implementation of the method makes it possible to conclude on its performance both at the stage of modernization of the information system of the organization and at the stage of development of the new system.